Design and Synthesis of Novel Spiro-Piperidinyl Pyrazolone Derivatives and Their Potential Antiviral Activity - Srinivasan, Rajagopalan; Narayana, Badiadka; Kunhanna Sarojini, Balladka; Bhanuprakash, Veerakyathappa; Govindaraju Darshan Raj, Chenna; S. Nayak, Prakash (Letters in Drug Design & Discovery, 2016)
A series of novel spiro-piperidinyl pyrazolones were synthesized starting from the commercially available ethyl nipecotate. The Boc protected ethyl nipecotate was reacted with 5-bromo-2-furaldehyde in the presence of LDA to afford the β -hydroxy ester which was converted to the β -keto ester by oxidation using manganese dioxide. Furthermore, β-keto ester was treated with hydrazine to form the spiro-piperidinyl pyrazolone scaffold. The phenyl/heteroaryl substituted (6ai) and hetero/arylethynyl substituted (7a-d) spiro pyrazolone were prepared by Suzuki and Sonogashira coupling followed by deprotection of the protecting group. All the synthesized compounds were evaluated for their invitro antiviral activity against BPXV on Vero cells. Compound 6c, 6d and 7c in the series showed potent antiviral activity.
Keywords: sonogashira coupling